Patterns of Disease Presentations in an Adult Outpatient Neurology Clinic of a Neurologist - Gajurel, Bikram Prasad; Karn, Ragesh; Rajbhandari, Reema; Ojha, Rajeev (Med Phoenix, 2022)
Introduction: Neurological disorders are very common all over the world. The most common neurological disorders causing maximum disability in Nepal are migraine and tetanus whereas the most common neurological causes of death are ischemic strokes and primary intracerebral hemorrhage. This small-scale study has been carried out to find out the frequency and types of disorders presenting in adult outpatient neurology clinic in a tertiary care hospital in Nepal. Materials and Methods: This is a retrospective descriptive study carried out in the outpatient department of the department of neurology at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The diseases were classified based on the 11th revision of the International Classification of Diseases. Chi-square test and Fisher’s exact test were used to calculate the significance of the different types of variables when applicable. Results: Of 1939 patients seen over a period of 12 months, diseases of the musculoskeletal system were the commonest (28.7%) followed by headache disorders (18.4%). Diseases of the musculoskeletal system, ischemic stroke, primary intracerebral hemorrhage, movement disorders, diseases of the inner ear were more common in patients more than 50 years and headache disorders; mental, behavioral or neurodevelopmental disorders; seizures and multiple sclerosis or other white matter disorders were more common patients aged 50 years or less. These differences were statistically significant. Conclusion: Almost all types of neurological disorders were seen in the adult outpatient neurology clinic providing the opportunity to carry out research and to uplift academic activities in a tertiary care hospital.